Minimally invasive treatment of old femoral fractures in adults. Issue 4 (April 2019) - Zhang, Xiang; Shui, Wei; Ni, Weidong; Hu, Zhenming; Huang, Wei; Luo, Gang; Qiao, Bo; Guo, Shuquan
Highlights: Minimally invasive treatment is feasible for most patients with old femoral fractures of the trochanter and femoral shaft. Minimally invasive surgery for old femoral fractures has the advantages of small incision, less bleeding, no bone grafting. Minimally invasive surgery respects the biological characteristics of bone and provides a good demonstration for the treatment of old limb fractures. Abstract: Objective: Extensive incision associated with large-scale callus exfoliation and internal fixation is the common therapeutic approach employed by the majority of orthopaedists in the treatment of old femoral fractures. Inspired by the surgical techniques of intramedullary fixation and reduction by traction, the present study attempted to treat old femoral fractures with minimally invasive methods utilising the principles of biological osteosynthesis (BO). Methods: A retrospective analysis involving 16 patients with old femoral fractures treated with combined traction, small incision, limited callus treatment, reduction by leverage and intramedullary fixation was conducted. The operative effect was evaluated by the operation time, intraoperative blood loss, bone grafting, healing time of fractures during follow-up, VAS score, and Harris hip score. Results: Intraoperative observation revealed an average operation time of 1.53 ± 0.34 h and average blood loss of 268.13 ± 97.29 ml without bone grafting in all patients. All enrolled patients had outcomes resulting in effective fixation restoration of limb alignment. Of the 16 enrolled patients, 13 patients completed follow-up with an average follow-up time of 7.42 ± 3.29 months. The average healing time for proximal femoral fractures was 3 months. The average healing time of femoral shaft fractures was 4 ± 1.09 months; two of these cases took 4 months to heal, whereas 1 case demonstrated a delayed healing time of 6 months. The VAS score was 1.15 ± 1.70, 1 patient experienced sciatica, and the Harris hip score was 92.92 ± 5.42. There were no complications of malunion, nonunion or infection among any of the patients who completed follow-up. Conclusions: Minimally invasive treatment is feasible for most patients with old femoral fractures of the trochanter and femoral shaft. This finding is consistent with BO principles, thereby providing a possible new method for the treatment of old femoral fractures.